Museum Sejarah Purbakala Pleret Sebagai Sarana Pembelajaran Sejarah - Iskandar Iskandar; Djoko Suryo (HEURISTIK: Jurnal Pendidikan Sejarah, 2021)
This research aims to know (1) the various collections in the Sejarah Purbakala Pleret Museum, (2) the relevance of the collections in the Sejarah Purbakala Pleret Museum with the subjects of history, and (3) the utilization of Sejarah Purbakala Pleret Museum as a means of studying history. This is qualitative research with constructivist approach. The results of the research show that Sejarah Purbakala Pleret Museum has 198 collections and 4 sites. The collection has a relevance to the materials of history lessons from the Pre-historic, Buddhist, Hindu, Islamic, to Dutch Colonial era. Learning history that can be done is by portfolio, PjBL, and scientific papers. The history of learning in Sejarah Purbakala Pleret Museum has not been implemented optimally. It is influenced by several factors namely a) limited Indonesia History compulsory lessons, b) permission issues from the school, c) long distance from the school, d) surveillance to students that is increasingly difficult, and e) the subject matter of history does not address directly to Pleret.